Geospatial data and model results for a global model study of coastal groundwater discharge - Elco Luijendijk; Tom Gleeson; Nils Moosdorf (PANGAEA, 2019)
This dataset contains 1) results of a series of model runs that explore the sensitivity coastal groundwater discharge to hydrogeological parameters, 2) results of a large series of numerical models of coastal groundwater discharge that cover parameter space for topographic gradients, recharge and permeability of coastal groundwater systems and 3) the results of a global geospatial data analysis of relief, watershed geometry, recharge and permeability of coastal watersheds, and values for coastal groundwater discharge that are based on a combination of the model experiments and the geospatial data analysis. A description of the methods that were used to generate these datasets can be found in a preprint on eartharxiv, see linked publication below.
Supplement to: Luijendijk, E et al. (2019): The Flow of Fresh Groundwater and Solutes to the World extquotesingles Oceans and Coastal Ecosystems. EarthArXiv Preprints, https://doi.org/10.31223/osf.io/sw8r4